# math ALGEBRA

posted by .

Solve by graping the foll:
A. 2X+Y=5
3X-Y=10

B.2X=Y+1
2X-Y=5

I don't know what "graping the foll" is, but problem #2 has no solution, because the lines

Y = 2X -1 (from your fist equation) and
Y = 2x -5 (from your second equation)
never intersect.

gas

## Similar Questions

1. ### algebra 1

Solve the Foll by substitution x=1/5y 3x+2y=26 So, substitute 1/5y for x in the second equation. Then solve for y. Can you take it from here?
2. ### French 1

I have to translate the foll phrase into french and then rewrite them using possive instead of de and the prepositional phrase 1. THE CASTLE OF THE KING a.Le chateau dole roi b.?
3. ### algebra

solve the system by graphing x+y=4 y=2x+1 I think these are the kind that you take equation #1 and rewrite it as y = -x + 4 and do the table for it plot the dots and connect the line for it. then take equation #2 y= 2x+ 1 do the table …
4. ### ap algebra

Please help me with this problem. I don't know what to do. Use the graph or table to determine a solution of the equation. Use synthetic division to verify that this number is a solution of the equation. Then solve the polynomial equation. …
5. ### Math

Did I do this problem correctly? Solve the following system by first handling the equation of the two lines: x=(0, 2) y=(-2, 1) x=(0, -1) y=(-3, -2) Equation 1: y= -x1 Equation 2: y=4x/3+2T Is this the correct answer?
6. ### ALGEBRA

If I am dividing the following: x^2+3x over x^2+2x-3 by x over x+1.. i know to do the recip. of x over x+1 and get the foll. x^2 + 3x over x^2 + 2x -3 times x+1 over x... now (x^2+3x)(x+1) over (x^2+2x-3)(x) now x(x+2)(x+1) x(x+2)(x-1) …
7. ### chemistry

complete and balance chemical equation for each of the foll A CH3_CHOH_CH3 --H2SO4--> B CH3_CHBr_CH3+koH-->
8. ### chemistry

complete and balance chemical equation for each of the foll A CH3_CHOH_CH3 --H2SO4--> B CH3_CHBr_CH3+koH-->
9. ### Chemistry

Please help...entrance exam soon Write the oxidation and reduction half reactions(showing e- lost or gained) for the foll O3 + I- -> IO3- + O2 (acidic)